The Influence of Entrepreneurial Orientation and Market Orientation on Business Performance Moderated by Government Support Policy - Eri Bukhari; Asep Hermawan; Sarfilianty Anggiani (International Journal of Business, Economics, and Social Development, 2026)
The objectives of this study are to analyze the moderating role of government support policy on business performance micro enterprises in the city of Bekasi with independent variables, namely entrepreneurial orientation and market orientation. This study uses a quantitative method with a non-probability sampling approach and purposive sampling technique, where the unit of analysis is the owner/leader of micro businesses. The number of samples that can be processed is 100 respondents. The collected data is analyzed using SmartPLS version 4. The findings of this study indicate that there is an influence of entrepreneurial orientation and market orientation on business performance. Government support policy was able to moderate the influence on business performance, but was unable to moderate the influence of entrepreneurial orientation on business performance. The theoretical implication of this study is that the moderating role of government support policy is a concrete manifestation of formal institutions that function as the main external context for the business performance of micro-businesses in the city of Bekasi. The limitations of this study are that the respondents were only owners/leaders of micro businesses in the Bekasi city area, with limited variables and research methods. Further research is recommended to involve more MSMEs with a wider geographical coverage, develop a research model with other exogenous variables, and be conducted using qualitative or mixed methods research.